Qualidade do transporte público urbano por ônibus: um estudo sobre a percepção dos usuários e o desempenho técnico em João Pessoa-PB - Freitas, Paulo Vitor Nascimento de (2016)
Worldwide the issue of urban mobility has been much discussed. Cities grow, and with them the need for a more rational, sustainable, efficient, good quality transport system. However, in Brazil, urban mobility problems have worsened increasingly in large and medium-sized urban centers, resulting mainly from the sprawling and inefficient growth of cities, loss of attractiveness of urban public transport, because of their low quality and prioritization of the car in intra-urbans shifts. In João Pessoa, mid-sized city, state capital of Paraiba, these phenomena can be observed. Thus, the general objective of this study was to evaluate the quality of the Public Transportation System by Bus of João Pessoa (PB), according to the perception of users and its technical performance. The specific objectives were to discuss the issue of urban mobility and specific issues of public transport; describe the organization of the Public Transportation System by bus in João Pessoa; check the views of system users and evaluate the perception they have about the quality; and evaluate the technical performance of the system according to quantitative and qualitative parameters. The quality attributes studied were: accessibility, frequency of service, travel time, capacity, reliability, security, vehicle characteristics, characteristics of bus stops, information system, connectivity, operators' behavior, cost to the user and status of routes. The methodology for evaluating the perception of users was based on the survey method, and the views of users captured by questionnaires. For the evaluation of technical performance, were used statistical and geospatial analysis tools, field research and evaluation techniques found in national and international literature. The assessment of perception showed that for users, the most critical factors are the cost (fare), security with regard to acts of violence (such as robberies and assaults) and capacity, while the accessibility, connectivity and behavior of operators got the best ratings. From a technical point of view, they stood out positively physical accessibility, related to satisfactory spatial coverage of bus stops, and safety linked to traffic accidents, with rates ranging from regular to good; whereas, among the attributes that had more problems, were can highlight the capacity, at least for a few lines in certain periods, the information system, which mainly hinders the unusual use of the service, and the cost to the user, result of a pricing model that is trapped in a dangerous vicious circle.